IS THE PRICE OF RAW MILK, AS SET BY THE ISRAELI GOVERNMENT THE OPTIMAL PRICE? - Tal SHAHOR; David DRORY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study examines the question of how the price of milk is determined in Israel. As in many countries, the Israeli government intervenes in the raw milk industry. This intervention is expressed as the setting of production quotas as well as the establishing of the price which farmers will receive for the raw milk. According to accepted economic theory, the optimal price is that which is established in the free market, which is to say, the price which is equal to the marginal cost. If the price is set above the marginal cost, then the producers have excess profit at the expense of the consumers. The purpose of this study is to determine if the price of raw milk which has been set by the Israeli government is a reasonable price. A previous study conducted in this field examined this issue using the number of cows the farmers raise. This study examines the same question using a different input, which is the amount of dry matter which is fed to the cows. The results of this study show that the price of raw milk is less than the marginal cost. Therefore, it appears as if the price of raw milk is too low, or that the farmers are not efficiently making use of the feed which is given to the cows.